Poverty and Prejudice Religious Inequality and the Struggle for Sustainable Development - Tadros, Mariz; Mader, Philip; Cheeseman, Kathryn (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book offers a comprehensive overview of how efforts to achieve SDGs can be enhanced by paying greater attention to freedom of religion and belief. In particular, it illustrates how poverty is often a direct result of religious prejudice and how religious identity can shape a person's job prospects, their children's education and the quality of public services they receive.